Selpercatinib in RET-fusion positive metastatic non-small cell lung cancer: achievements and gray areas. Issue 8 (3rd August 2022) - Belluomini, Lorenzo; Avancini, Alice; Pasqualin, Luca; Insolda, Jessica; Sposito, Marco; Menis, Jessica; Tregnago, Daniela; Trestini, Ilaria; Ferrara, Miriam Grazia; Bria, Emilio; Milella, Michele; Pilotto, Sara
ABSTRACT: Introduction: Selpercatinib is a RET selective tyrosine kinase inhibitor with nanomolar potency against diverse RET alterations, including fusions, activating point mutations, and acquired resistance mutations. Rearranged during transfection (RET) gene is a validated target in non-small-cell lung cancer (NSCLC). Selpercatinib is currently approved for adult patients with metastatic RET fusion-positive NSCLC. Areas covered: This review summarizes the efficacy and safety data of selpercatinib in the treatment landscape of RET fusion-positive NSCLC. Expert opinion: Globally considered, selpercatinib is an optimal treatment choice, in terms of both (systemic and intracranial) efficacy and safety, in patients affected by advanced NSCLC harboring RET fusions as a driver mechanism. Future challenges include the identification of the most appropriate placement for selpercatinib in the treatment algorithm of RET fusion-positive NSCLC (including early stages), the clarification of resistance mechanisms, as well as of its role in EGFR-mutant NSCLC undergoing progression during osimertinib driven by RET alterations.